2007
DOI: 10.1038/modpathol.3800834
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation profiles of protein kinases in alveolar and embryonal rhabdomyosarcoma

Abstract: Rhabdomyosarcoma is the most common pediatric soft-tissue sarcoma, which includes two major subtypes, alveolar and embryonal rhabdomyosarcoma. The mechanism of its oncogenesis is largely unknown. However, the oncogenic process of rhabdomyosarcoma involves multi-stages of signaling protein dysregulation characterized by prolonged activation of tyrosine and serine/threonine kinases. To better understand this protein dysregulation, we evaluated the phosphorylation profiles of multiple tyrosine and serine/threonin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
36
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 36 publications
2
36
0
Order By: Relevance
“…EphB4 has previously been identified to contribute toward tumor suppression, apoptosis, or an increased malignant phenotype in a variety of other cancers (4-6, 9, 11, 27, 28). In our studies, we further identified a previously undescribed mechanism of cross-talk between EphB4 with another RTK, PDGFRβ, which is known to be activated and expressed in aRMS (29,30).…”
Section: Discussionmentioning
confidence: 86%
“…EphB4 has previously been identified to contribute toward tumor suppression, apoptosis, or an increased malignant phenotype in a variety of other cancers (4-6, 9, 11, 27, 28). In our studies, we further identified a previously undescribed mechanism of cross-talk between EphB4 with another RTK, PDGFRβ, which is known to be activated and expressed in aRMS (29,30).…”
Section: Discussionmentioning
confidence: 86%
“…27,28 Furthermore, it was reported that cases of chordoma and synovial sarcoma displayed strong expression of EGFR, 29,30 and that these cases could be successfully treated by therapies targeting EGFR signaling. 30 These observations imply that aberrant EGFR/mTOR signaling may also be involved in the pathology of other defined subsets of bone and soft tissue tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Inactivation of PKCθ leads to increased susceptibility to obesity and dietary insulin resistance in mice [53,54], and impaired anti-leukemic immune response [55]. We find that unlike other types of cancer, PKCθ in HCC is downregulated [48][49][50][51][52]. These discrepancy maybe due to increase susceptibility of insulin resistance which favors the survival of HCC cells.…”
Section: Discussionmentioning
confidence: 63%
“…PKCθ regulates AKT signaling pathway and KIT expression [48]. Overexpression of PKCθ may result in cancer development [48][49][50][51][52]. Inactivation of PKCθ leads to increased susceptibility to obesity and dietary insulin resistance in mice [53,54], and impaired anti-leukemic immune response [55].…”
Section: Discussionmentioning
confidence: 99%